Performance persistence: The case of Colombia’s pension and severance pay funds (2011)
This paper studies performance persistence for mandatory, voluntary and severance pay funds in Colombia. We test for persistence in terms of raw and style-adjusted returns for consecutive and mul - tiple periods. This document also explores whether an investor following strategies based on persistence can attain statistical and economically significant excess returns. Our results indicate the presence of performance persistence for some funds in the very short run. However, investors pursuing portfolio strategies based on this sort of predictability would have been unable to obtain significant excess returns. More importantly, these findings support the notion of weak-form market efficiency.